Experimental Determination of the QCD Effective Charge αg1(Q) - Alexandre Deur; Volker Burkert; Jian-Ping Chen; Wolfgang Korsch (Particles, 2022)
The QCD effective charge <semantics>αg1(Q)</semantics> is an observable that characterizes the magnitude of the strong interaction. At high momentum Q, it coincides with the QCD running coupling <semantics>αs(Q)</semantics>. At low Q, it offers a nonperturbative definition of the running coupling. We have extracted <semantics>αg1(Q)</semantics> from measurements carried out at Jefferson Lab that span the very low to moderately high Q domain, <semantics>0.14≤Q≤2.18</semantics> GeV. The precision of the new results is much improved over the previous extractions and the reach in Q at the lower end is significantly expanded. The data show that <semantics>αg1(Q)</semantics> becomes Q-independent at very low Q. They compare well with two recent predictions of the QCD effective charge based on Dyson–Schwinger equations and on the AdS/CFT duality.